Integrated Process of Palm Oil Mill Effluent using Electrocoagulation, Active Carbon Filter, Zeolite and Membrane Separation Technology - Kemas Uwais Alqorni; Hatta Dahlan; Susila Arita (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2024)
Palm Oil Mill Effluent (POME) is a type of agro-industrial organic originating from the by-products of the processing of fresh fruit bunches (FFB) of oil palm. Palm oil waste pollution decreases environmental quality which will indirectly be harmful to the environment and human health. This research aims to treat palm oil liquid waste using electrocoagulation process, activated carbon filter, zeolite and membrane separation technology in an integrated manner. The combination of palm ash and zeolite was found to be the most effective in reducing pH, TSS, COD, BOD, and fatty oils. The electrocoagulation method best conditions are at a voltage of 15 Volts and an operating time of 90 minutes. The system of integration of the electrocoagulation process, activated carbon filters, zeolite and membrane separation technology has proven to be very effective for processing palm oil mill wastewater. The treatment results meet the quality standards based on Governor of South Sumatra Regulation No. 8 of 2012 concerning Liquid Waste Quality Standards for Industrial, Hotel, Hospital, Domestic and Coal Mining Activities and based on Government Regulation no. 22 of 2021 concerning Implementation and Management of the Environment (Annex 6 National Water Quality Standards) with average results: pH 7.02 TSS 44.6 mg/L, COD 24 mg/L, BOD 2.89 mg/L and fatty oils 1.2 mg/LKeywords: Palm Oil Mill Effluent, Electrocoagulation, Zeolite, UF Membrane, Fatty Oil